EDUCATION AND PUBLIC SECURITY: THE CHALLENGE OF THE PEDAGOGUE’S ROLE IN THE TRAINING OF MILITARY POLICE OFFICERS WITH THE CONTENT OF HUMAN RIGHTS - Castiajo, Daniel (Revista Gênero e Interdisciplinaridade, 2026)
This paper proposes a reflection on the challenge of the pedagogue’s role as a mediator of knowledge in the continuing education of military police officers working in the Baixada Fluminense, a peripheral area of ​​Rio de Janeiro. It is an offshoot of ongoing doctoral research in Education, Culture and Communication. An interdisciplinary approach methodology is adopted, articulating bibliographic research with the production of qualitative data derived from observational participation in the exercise of the teaching function in Public Security. The study aims to examine how knowledge surrounding human rights can be worked on with the purpose of re-signifying conceptions and ideas originating from common sense among military police officers working in peripheral areas of Rio de Janeiro. The theoretical framework is based on authors such as Paulo Freire, Tiaraju D’Andrea, Alba Zaluar, Jacqueline Muniz, Elizabete Albernaz and Carlos Magno Nazareth Cerqueira, making it possible to analyze which approaches can be adopted as strategies for the professional improvement of military police officers engaged with the theme of human rights. Preliminary results indicate that a considerable portion of military police officers, in most classes, demonstrate resistance to the topic, pejoratively attributing it to "human rights personnel" and non-governmental organizations, personifying them as "groups that only serve to defend criminals." Such positions reinforce a "warrior ethos" that perpetuates itself in the cultural context within the barracks and manifests itself in daily police work, making the educator’s task challenging in terms of knowledge production and offering plausible alternatives for the relationship between the police and society, in favor of promoting human rights.